ANALISIS PENGEMBANGAN USAHA BENGKEL MOTOR DI JALAN DARMA BAKTI KECAMATAN PAYUNG SEKAKI - Damanik, Charry K.; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to analysis the development of a motorbike workshop business in Jalan Darma Bakti, Payung Sekaki District. The motorcycle repair shop at Jalan Darma Bakti, Payung Sekaki District, to find out the characteristics of the people who came to the motorbike repair shop and the dominant factors in developing a motorbike workshop business. In this study, researchers used a type of descriptive quantitative research. The location at Jalan Darma Bakti in Payung Sekaki Subdistrict, the participation of this study was 360 people and those taken as samples in this study were 10% so that the sample was taken 36 people and the sample was taken using simple random sampling. The technique of collecting data is using observation, questionnaires or questionnaires, and interviews. The results of this study proved that the development of a motorbike workshop business in supporting its business uses banners, maximum service and results as well as low prices for service services. The dominant factor in the development of a motorbike workshop business is service. Keywords: Analysis, Service, Motorcycle Repair Development